Invisible at Home and in Society: Social Exclusion Experiences of Children with Disabilities - Omorogiuwa, Trace B.E.; Aladeselu, Osayuwamen Adewale (NIU Journal of Social Sciences, 2025)
Children with disabilities face multifaceted social exclusion across various domains of life, particularly in low-resource urban settings in Nigeria. This conceptual paper explores how children with disabilities experience exclusion within the home, school, and community. Drawing from social exclusion theory and Bronfenbrenner’s ecological systems theory, the paper critically examines the interplay of cultural stigma, poverty, gender dynamics, and institutional gaps that reinforce their marginalization. Emphasis is placed on how these factors manifest differently across gender lines and how they contribute to the invisibility of these children in both private and public spaces. The study identifies limitations in current policies, inadequate support structures for caregivers, and societal misconceptions about disability. It proposes family-centered and community-based social work strategies, including inclusive education advocacy, caregiver psychosocial support, and public sensitization campaigns. The paper concludes with actionable recommendations for social workers, policymakers, and development actors committed to disability inclusion. Keywords: Social Exclusion, Children with disabilities, Family, Social Work, Gender.